Discord And Direction The Postmodern Writing Program Administrator - Mcgee, Sharon James; Handa, Carolyn (University Press of Colorado, 2005)
The argument of this collection is that the cultural and intellectual legacies of postmodernism impinge, significantly and daily, on the practice of the Writing Program Administrator. WPAs work in spaces where they must assume responsibility for a multifaceted program, a diverse curriculum, instructors with varying pedagogies and technological expertise-and where they must position their program in relation to a university with its own conflicted mission, and a state with its unpredictable views of accountability and assessment. The collection further argues that postmodernism offers a useful lens through which to understand the work of WPAs and to examine the discordant cultural and institutional issues that shape their work. Each chapter tackles a problem local to its author's writing program or experience as a WPA, and each responds to existing discord in creative ways that move toward rebuilding and redirection. It is a given that accepting the role of WPA will land you squarely in the bind between modernism and postmodernism: while composition studies as a field arguably still reflects a modernist ethos, the WPA must grapple daily with postmodern habits of thought and ways of being. The effort to live in this role may or may not mean that a WPA will adopt a postmodern stance; it does mean, however, that being a WPA requires dealing with the postmodern.